Rectus Muscle Hematoma as a Rare Differential Diagnosis of Acute Abdomen; a Case Report - Maleki-Verki, Mohammadreza; Motamed, Hasan (Archives of Academic Emergency Medicine, 2018)
Rectus sheath hematoma is a rare but well-known problem. Exercise, pregnancy, subcutaneous injection of insulin, abdominal surgery and severe coughs can be predisposing factors of hemorrhage in the mentioned muscle sheath. Here, we will discuss a case of rectus sheath hematoma in a 28 year-old female patient who presented to emergency department with complaint of abdominal pain and improved in 1 week with palliative care.